Bahasa Arab : Identitas, Dinamika, dan Transformasinya dalam Peradaban Global - Amin, Azkiya Rafida (Maliki Interdisciplinary Journal, 2026)
Arabic is a language that plays a strategic role in the formation of identity, the development of knowledge, and the dynamics of global civilization. This article aims to examine the position of the Arabic language as a pillar of Islamic identity, to trace its development from Classical Arabic to Modern Arabic, and to analyze its transformation within the context of contemporary global civilization. This study employs a descriptive qualitative approach using a library research method. Data were obtained through a critical review of books, journal articles, and scholarly documents relevant to Arabic linguistics, the history of Islamic civilization, and sociolinguistics. Data analysis was conducted using the interactive model proposed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that Arabic possesses strong adaptive capabilities without losing its standard linguistic characteristics. Classical Arabic continues to function as a normative reference, while Modern Arabic has developed as a medium of scientific and global communication. This transformation demonstrates that Arabic not only survives amid modernization but also actively participates in various aspects of global life, including education, diplomacy, and technology.